Emission properties of suprathermal electrons produced by laser–plasma interactions. (26th October 2017) - Liu, Huiya; Kang, Ning; Zhou, Shenlei; An, Honghai; Fang, Zhiheng; Xiong, Jun; Li, Kun; Lei, Anle; Lin, Zunqi
Abstract: Suprathermal electrons produced by laser–plasma interactions at 0.53-μm laser wavelength have been investigated using 19 electron spectrometers. The targets were 2- and 10-μm-thick Al foils, while the laser average intensities were 2 × 10 13 and 7 × 10 14 W/cm 2 . A double temperature distribution was observed in the electron energy spectrum: the lower electron temperature was below 25 keV, whereas the higher was 50 keV. The angular distribution of the total suprathermal electron energy approximately obeyed the Gaussian distribution, peaking along thek vector of the incident laser beam for perpendicular incidence. Furthermore, the conversion rate of laser energy into escaped suprathermal electron energy over the π sr solid angle was 10 −4 at \!\!10^14 W/cm^2, increasing almost linearly with the laser intensity.